Предмет: Алгебра,
автор: Аноним
Помоги пожалуйста если знаешь. Я прошу пожалуйста, мне очень нужно♡ (15 баллов даю) Пожалуйста!
Приложения:
Ответы
Автор ответа:
0
f`(x)=x^2+x+1+(x-1)*(2x+1)=x^2+x+1+2x^2-x-1=3x^2
g`(x)=(2(x+3)-2x)/(x+3)^2=(2x+6-2x)/(x+3)^2=6/(x+3)^2
g`(-2)=6/1=6
f`(x)-g`(-2)=3x^2-6=0
3(x^2-2)=0
x=+-√2
Похожие вопросы
Предмет: Русский язык,
автор: милана1203
Предмет: Русский язык,
автор: НастяяяяяяЯяяя234
Предмет: Русский язык,
автор: loura210
Предмет: Математика,
автор: 12345678256